Waqf as a Tool for Climate Change Mitigation in Northern Nigeria - Muhammad, Adamu Abubakar; Ibrahim, Aliyu; Mohammed, Yakubu Zulaihat; Yakub, Abubakar Aliyu (IDRIS Darulfunun Institute, 2025)
As the world grapples with the escalating impacts of climate change, innovative financing mechanisms to support mitigation efforts have become increasingly urgent. This study investigates the potential role of waqf an Islamic endowment system in addressing climate change challenges in Northern Nigeria, a region that faces a number of environmental and climate challenges particularly in terms of environmental degradation and climatic variability. The research utilizes a mixed-methods approach, combining qualitative interviews with key stakeholders, including waqf administrators, community leaders, and environmental activists, alongside quantitative analysis of existing waqf funds and projects related to climate adaptation. Findings reveal that waqf funds can be effectively leveraged to support various climate change mitigation initiatives, such as afforestation, water conservation, and renewable energy projects. The study highlights several successful case studies where waqf-supported activities have enhanced local resilience and contributed to sustainable resource management. Furthermore, it identifies significant barriers to the implementation of environmentally focused waqf initiatives, including lack of awareness, inadequate regulatory frameworks, and limited community engagement. The paper proposes actionable recommendations to optimize the role of waqf in climate change mitigation, including enhancing legal structures to support environmental waqf, fostering collaboration between waqf institutions and environmental NGOs, and implementing educational campaigns to raise awareness about the importance of sustainable practices within waqf management. Ultimately, this study advocates for a paradigm shift in the perception of waqf from a purely charitable endeavor to a comprehensive instrument for sustainability and climate resilience, thereby contributing to the broader discourse on integrating indigenous financial mechanisms into global climate change strategies.